Experimental envenomation with Crotalus durissus terrificus venom in dogs treated with antiophidic serum - Part II: Laboratory aspects, electrocardiogram and histopathology - Nogueira, Rosa Maria Barilli; Sakate, M. [UNESP]; Sangiorgio, F.; Laposy, C. B.; Tostes, R. A. (FapUNIFESP (SciELO), 2007)
The present work shows laboratory aspects, electrocardiogram and histopathology results during experimental envenomation by Crotalus durissus terrificus in dogs treated with antiophidic serum. Twenty-one dogs were divided into three groups of seven animals each. Group I received 1mg/kg venom (sc); Group II received 1mg/kg venom (sc), 50mg antiophidic serum (iv) and fluid therapy including 0.9% NaCl solution (iv); and Group III received 1mg/kg venom (sc), 50mg antiophidic serum (iv) and fluid therapy including 0.9% NaCl solution containing sodium bicarbonate diluted to the dose of 4mEq/kg. Urinalysis showed brown urine, proteinuria, occult blood and myoglobinuria. Respiratory acidosis and hypotension were also observed. At the venom inoculation site, there was discreet edema, popliteal lymph node response, musculature presenting whitish areas and necrotic myositis with myoregenerative activity. There was not evidence of electrocardiographical and biochemical alterations.
Keywords: Crotalus durissus terrificus; Dog; Histopathology; Laboratory aspects; Animalia; Canis familiaris